제1형의 우측중도절단된 와이블 수명자료를 관리하는 이항 누적합 관리도 - 최민재; Min-jae Choi; 이재헌; Jae Heon Lee (Ŭngyong tʻonggye yŏnʼgu, 2016)
제품의 수명은 품질을 나타내는 중요한 특성치이다. 이상적으로는 모든 표본의 수명자료를 측정하는 것이 가장 바람직하나, 이를 측정하는데 많은 시간과 비용이 소요되는 경우 중도절단된 자료로 표본을 구성하는 경우가 많이 발생한다. 이 논문에서는 제1형의 우측중도절단된 수명자료가 와이블 분포를 따를 경우 척도모수의 감소를 탐지하는 이항 누적합 관리도 절차를 제안하였다. 모의실험에서 평균런길이를 이용하여 제안된 관리도 절차의 효율을 이전에 연구된 누적합 관리도 절차와 비교하였는데, 그 결과 중도절단율이 높을 경우와 표본의 크기가 적은 경우 제안된 이항 누적합 관리도가 더 효율적임을 알 수 있었다. The lifetime is a key characteristic of product quality. It is best to obtain the lifetime data of all samples, but they are often censored due to time or expense limitations. In this paper, we propose a binomial cumulative sum (CUSUM) chart to monitor the mean of type I right-censored Weibull lifetime data, for a _xed value of the Weibull shape parameter. We compare the performance of the proposed binomial CUSUM chart with CUSUM charts studied previously using the steady-state average run length (ARL). The results show that the performance of the binomial CUSUM chart is better when the censoring rate is high and/or the sample size is small.